HPV16 E6 oncoprotein‐induced upregulation of lncRNA GABPB1‐AS1 facilitates cervical cancer progression by regulating miR‐519e‐5p/Notch2 axis. Issue 10 (26th August 2020) - Ou, Rongying; Lv, Mingfen; Liu, Xuan; Lv, Jiangmin; Zhao, Jinduo; Zhao, Ye; Li, Xiangyun; Li, Wenfeng; Zhao, Liang; Li, Jianrong; Ren, Yi; Xu, Yunsheng
Abstract: Human papillomaviruses 16 (HPV16) is the primary causative agent of cervical cancer (CC). E6 oncoprotein plays a crucial role in cervical carcinogenesis and commonly cause the dysregulation of the long noncoding RNAs (lncRNAs) expression. However, the biological function of lncRNAs in HPV16‐related CC remains largely unexplored. In the present study HPV16 E6‐induced differential expression of lncRNAs, miRNA, and mRNA were identified using microarray‐based analysis and verified in tumor r cell lines and tumor tissues, and the function of lncRNA in CC was investigated in vitro and in vivo. We found that an lncRNA, named GABPB1‐AS1, was significantly upregulated in HPV16‐positive CC tissues and cell lines. GABPB1‐AS1 expression in HPV16‐positive CC tissues was positively associated with tumor size, lymph node metastasis, and FIGO stage. High expression of GABPB1‐AS1 was correlated with a poor prognosis for HPV16‐positive CC patients. Functionally, E6‐induced GABPB1‐AS1 overexpression facilitated CC cells proliferation and invasion in vitro and in vivo. Mechanistically, GABPB1‐AS1 acted as a competing endogenous RNA (ceRNA) by sponging miR‐519e‐5p, resulting in the de‐repression of its target gene Notch2 which is well known as an oncogene. Therefore, GABPB1‐AS1 functioned as a tumor activator in CC pathogenesis by binding to miR‐519e‐5p and destroying its tumor suppressive function. Collectively, current results demonstrate that GABPB1‐AS1 is associated with CC progression, and may be a promising biomarker or target for the clinical management of CC.